2022
DOI: 10.1155/2022/7169353
|View full text |Cite
|
Sign up to set email alerts
|

Role of Long Noncoding RNAs in Smoking-Induced Lung Cancer: An In Silico Study

Abstract: The prevalence of lung cancer induced by cigarette smoking has increased over time. Long noncoding (lnc) RNAs, regulatory factors that play a role in human diseases, are commonly dysregulated in lung cancer. Cigarette smoking is closely related to changes in lncRNA expression, which can affect lung cancer. Herein, we assess the mechanism of lung cancer initiation induced by smoking. To calculate the impact of smoking on the survival of patients with lung cancer, we extracted data from The Cancer Genome Atlas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Studies have shown that tobacco smoke increases somatic mutations in select genes, which may subsequently promote carcinogenesis [ 17 ]. In particular, past research has demonstrated that several molecular factors, such as eRNA, lncRNAs, and immune cells, may act as mediators of tobacco smoke-induced LUSC development [ 22 , 23 ]. However, despite the implications of these molecular factors on cancer malignancy, relatively few studies analyze tRF expression in LUSC with respect to etiological agents such as tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that tobacco smoke increases somatic mutations in select genes, which may subsequently promote carcinogenesis [ 17 ]. In particular, past research has demonstrated that several molecular factors, such as eRNA, lncRNAs, and immune cells, may act as mediators of tobacco smoke-induced LUSC development [ 22 , 23 ]. However, despite the implications of these molecular factors on cancer malignancy, relatively few studies analyze tRF expression in LUSC with respect to etiological agents such as tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, KRAS , p53 , and BRAF mutations, as well as mutations in the RAS/Rtk pathway, were found to be enriched in smokers when compared to non-smokers in NSCLC [ 21 ]. Previous research has also demonstrated that smoking is associated with alterations in the expression of long noncoding RNAs (lncRNA) with respect to lung cancer prognosis and survival rates [ 22 ]. Moreover, the expression of immune cells, including CD4 T cells and NK cells, was observed to be differentially regulated in smoking-induced LUSC patients when compared to non-smoking-induced LUSC patients, which may play a role in promoting tumor progression and altering interactions within the tumor microenvironment [ 20 ].…”
Section: Introductionmentioning
confidence: 99%